Quasi-experimental trial of diabetes Self-Management Automated and Real-Time Telephonic Support (SMARTSteps) in a Medicaid managed care plan: study protocol - Ratanawongsa Neda; Handley Margaret A; Quan Judy; Sarkar Urmimala; Pfeifer Kelly; Soria Catalina; Schillinger Dean (BMC, 2012)
Abstract Background Health information technology can enhance self-management and quality of life for patients with chronic disease and overcome healthcare barriers for patients with limited English proficiency. After a randomized controlled trial of a multilingual automated telephone self-management support program (ATSM) improved patient-centered dimensions of diabetes care in safety net clinics, we collaborated with a nonprofit Medicaid managed care plan to translate research into practice, offering ATSM as a covered benefit and augmenting ATSM to promote medication activation. This paper describes the protocol of the Self-Management Automated and Real-Time Telephonic Support Project (SMARTSteps). Methods/Design This controlled quasi-experimental trial used a wait-list variant of a stepped wedge design to enroll 362 adult health plan members with diabetes who speak English, Cantonese, or Spanish and receive care at 4 publicly-funded clinics. Through language-stratified randomization, participants were assigned to four intervention statuses: SMARTSteps-ONLY, SMARTSteps-PLUS, or wait-list for either intervention. In addition to usual primary care, intervention participants received 27 weekly calls in their preferred language with rotating queries and response-triggered education about self-care, medication adherence, safety concerns, psychological issues, and preventive services. Health coaches from the health plan called patients with out-of-range responses for collaborative goal setting and action planning. SMARTSteps-PLUS also included health coach calls to promote medication activation, adherence and intensification, if triggered by ATSM-reported non-adherence, refill non-adherence from pharmacy claims, or suboptimal cardiometabolic indicators. Wait-list patients crossed-over to SMARTSteps-ONLY or -PLUS at 6 months. For participants who agreed to structured telephone interviews at baseline and 6 months (n = 252), primary outcomes will be changes in quality of life and functional status with secondary outcomes of 6-month changes in self-management behaviors/efficacy and patient-centered processes of care. We will also evaluate 6-month changes in cardiometabolic (HbA1c, blood pressure, and LDL) and utilization indicators for all participants. Discussion Outcomes will provide evidence regarding real-world implementation of ATSM within a Medicaid managed care plan serving safety net settings. The evaluation trial will provide insight into translating and scaling up health information technology interventions for linguistically and culturally diverse vulnerable populations with chronic disease. Trial Registration ClinicalTrials.gov: NCT00683020